Preparation method of highly hygroscopic polyphenylene sulfide monofilament and highly hygroscopic polyphenylene sulfide monofilament
By introducing modified titanium dioxide and sodium acrylate grafted nanotitanium dioxide into the polyphenylene sulfide monofilament, the problem of chain fracture and static electricity easily occur under ultraviolet light irradiation is solved, and the high hygroscopicity and ultraviolet resistance are improved.
Patent Information
- Application Number
- CN202411573585.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Polyphenylene sulfide is prone to chain fracture under ultraviolet light, resulting in insufficient photoaging. At the same time, since there are no hygroscopic groups in the main chain structure, the spinning production process is prone to static electricity, affecting the material performance.
By preparing modified titanium dioxide and sodium acrylate grafted nanotitanium dioxide, mixed with polyphenylene sulfide resin, melt extrusion and spinning using a single screw spinning machine to form a highly hygroscopic polyphenylene sulfide monofilament.
The ultraviolet resistance and hygroscopicity of polyphenylene sulfide monofilament is improved, the electrostatic problem is reduced, the mechanical properties are ensured, and the hydrophilicity and hygroscopicity of the monofilament is enhanced.
Smart Images

Figure CN119061522B_ABST
Abstract
Description
Technical Field
[0001] The present invention generally relates to the field of monofilaments, and in particular to a method for preparing highly hygroscopic polyphenylene sulfide monofilaments and highly hygroscopic polyphenylene sulfide monofilaments. Background Art
[0002] Polyphenylene sulfide (full name: polyphenylene sulfide, English name: Polyphenylene Sulfide, abbreviated as PPS) is the largest variety of special engineering plastics. It is known as the "world's sixth largest engineering plastic" after polycarbonate (PC), polyester (PET), polyoxymethylene (POM), nylon (PA), and polyphenylene ether (PPO). It is also one of the eight major aerospace materials.
[0003] PPS is a white or beige, highly crystalline, hard and brittle polymer. The density of pure PPS is 1.34g / cm³. The density increases after modification. The melting point is 280℃-290℃, the glass transition temperature is about 110℃, the crystallinity is 55%-65%, the starting temperature of thermal decomposition in air is as high as 450℃, it has good flame retardancy, and the oxygen index is as high as 46%-53%. So far, no organic solvent that can dissolve PPS resin below 200℃ has been found. It has excellent chemical resistance and heat resistance, high dimensional stability, low hygroscopicity, and high hydrolysis resistance when exposed to acids, alkalis and organic solvents. This material can be used in areas that require excellent heat resistance and chemical resistance.
[0004] However, due to the large number of benzene ring structures in the PPS molecular chain, the molecular chain tension is very large, and the chain is prone to breakage when exposed to high-energy light, especially ultraviolet light, which is manifested as insufficient light aging resistance in the macroscopic sense. At the same time, there are no hygroscopic groups in the main chain structure of PPS, and the moisture regain is low, which leads to static electricity in the spinning production process. Therefore, materials with PPS added are prone to insufficient light aging resistance and static electricity. Summary of the invention
[0005] In view of the above-mentioned defects or deficiencies in the prior art, it is desirable to provide a method for preparing a highly hygroscopic polyphenylene sulfide monofilament and a highly hygroscopic polyphenylene sulfide monofilament.
[0006] In a first aspect, the present application provides a method for preparing a highly hygroscopic polyphenylene sulfide monofilament, comprising:
[0007] Preparation of modified titanium dioxide: activating a certain mass of nano titanium dioxide to obtain activated nano titanium dioxide, providing a silane coupling agent solution, adding the activated titanium dioxide into the silane coupling agent solution, reacting at a set temperature for a set time, and obtaining modified titanium dioxide;
[0008] Preparation of sodium acrylate grafted nano titanium dioxide: providing a sodium acrylate solution, placing the modified titanium dioxide into the sodium acrylate solution, adding an initiator to carry out stirring reaction until it becomes viscous, precipitating, washing and drying the product to obtain sodium polyacrylate grafted nano titanium dioxide;
[0009] Preparation of highly hygroscopic polyphenylene sulfide monofilaments: uniformly mix a certain mass fraction of polyphenylene sulfide resin slices, the sodium polyacrylate grafted nano-titanium dioxide, and a light stabilizer, add the mixture into a single-screw spinning machine, and perform melt extrusion spinning to obtain highly hygroscopic polyphenylene sulfide monofilaments.
[0010] As an achievable method, the “activating a certain mass of nano titanium dioxide to obtain activated nano titanium dioxide” includes: immersing a certain mass of nano titanium dioxide in a sodium methane sulfonate solution with a mass fraction of 5% for a certain period of time for activation treatment;
[0011] Then drying is performed to obtain activated nano titanium dioxide;
[0012] Wherein, the particle size of the nano titanium dioxide is 30-50nm.
[0013] As an achievable manner, the concentration of the silane coupling agent solution is 2%, and a mixture of ethanol and water is used, wherein the volume ratio of ethanol to water is 1:1.
[0014] As an achievable manner, the silane coupling agent is γ-(methacryloyloxy)propyltrimethoxysilane.
[0015] As an achievable manner, the light stabilizer is UV-3346 or UV-1084.
[0016] As an achievable method, the mass ratio of the polyphenylene sulfide resin slice, the sodium polyacrylate grafted nano-titanium dioxide and the light stabilizer is (95-98): (4-1): (4-1);
[0017] Wherein, the density of the polyphenylene sulfide resin slice is 1.34-1.36 g / cm 3 .
[0018] As an achievable manner, the single-screw spinning machine comprises a feed port, a screw zone and a spinning manifold arranged in sequence, the screw zone is provided with a melt extrusion port, and the melt extrusion port is connected to the spinning manifold through a bend pipe.
[0019] The melt extrusion port is provided with a melt metering pump, and the pump supply amount of the melt metering pump is 20-23 g / min.
[0020] In a second aspect, a method for preparing highly hygroscopic polyphenylene sulfide monofilaments is provided to prepare highly hygroscopic polyphenylene sulfide monofilaments.
[0021] According to the technical solution provided in the embodiment of the present application, by using sodium polyacrylate grafted nano-titanium dioxide as one of the components for preparing monofilaments, on the one hand, the nano-titanium dioxide shell is used to improve the UV resistance of polyphenylene sulfide monofilaments; on the other hand, the component is prepared by polymer grafting, and the polymer grafting method can inhibit the agglomeration of nano-titanium dioxide. During the melt spinning process, nano-titanium dioxide helps to reduce the size of the sodium polyacrylate dispersed phase, improve the dispersibility of sodium polyacrylate in polyphenylene sulfide, and help to form a moisture absorption path in the polyphenylene sulfide monofilament, thereby improving the hygroscopicity while ensuring the mechanical properties; on the third hand, the present application selects sodium polyacrylate and nano-titanium dioxide for grafting. Since sodium polyacrylate itself contains a large number of polar hydrophilic groups and has an affinity for water, and since sodium polyacrylate inhibits the crystallization of polyphenylene sulfide, the crystallinity is reduced and the amorphous area is increased, which is beneficial to the subsequent stretching step in the spinning process, increases the strength of the monofilament, and can also improve the hydrophilicity and hygroscopicity of the monofilament. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Other features, objects and advantages of the present application will become more apparent by reading the detailed description of non-limiting embodiments made with reference to the following drawings:
[0023] Figure 1 Flow chart of the method for preparing highly hygroscopic polyphenylene sulfide monofilament in this embodiment. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It is also necessary to explain that, for ease of description, only the parts related to the invention are shown in the accompanying drawings.
[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0026] Please refer to Figure 1 This embodiment provides a method for preparing a highly hygroscopic polyphenylene sulfide monofilament, the method comprising:
[0027] S10: preparing modified titanium dioxide: activating a certain mass of nano titanium dioxide to obtain activated nano titanium dioxide, providing a silane coupling agent solution, adding the activated titanium dioxide into the silane coupling agent solution, reacting at a set temperature for a set time, and obtaining modified titanium dioxide;
[0028] S20: preparing sodium acrylate grafted nano titanium dioxide: providing a sodium acrylate solution, placing the modified titanium dioxide into the sodium acrylate solution, adding an initiator to carry out stirring reaction until it becomes viscous, precipitating, washing and drying the product to obtain sodium polyacrylate grafted nano titanium dioxide;
[0029] S30: preparing highly hygroscopic polyphenylene sulfide monofilaments: uniformly mixing a certain mass fraction of polyphenylene sulfide resin slices, the sodium polyacrylate grafted nano-titanium dioxide, and a light stabilizer, adding the mixture into a single-screw spinning machine, and performing melt extrusion spinning to obtain highly hygroscopic polyphenylene sulfide monofilaments.
[0030] In this embodiment, sodium polyacrylate grafted nano-titanium dioxide is used as one of the components for preparing monofilaments. On the one hand, the nano-titanium dioxide shell is used to improve the UV resistance of polyphenylene sulfide monofilaments; on the other hand, the component is prepared by polymer grafting, and the polymer grafting method can inhibit the agglomeration of nano-titanium dioxide. During the melt spinning process, nano-titanium dioxide helps to reduce the size of the sodium polyacrylate dispersed phase, improve the dispersibility of sodium polyacrylate in polyphenylene sulfide, and help to form a moisture absorption path in the polyphenylene sulfide monofilament, thereby improving the hygroscopicity while ensuring the mechanical properties; thirdly, this application selects sodium polyacrylate and nano-titanium dioxide for grafting. Since sodium polyacrylate itself contains a large number of polar hydrophilic groups and has an affinity for water, and since sodium polyacrylate inhibits the crystallization of polyphenylene sulfide, the crystallinity is reduced and the amorphous area is increased, which is beneficial to the subsequent stretching step in the spinning process, increases the strength of the monofilament, and can also improve the hydrophilicity and hygroscopicity of the monofilament.
[0031] First, a certain amount of nano-titanium dioxide is immersed in a 5% sodium methane sulfonate solution for a certain period of time for activation treatment;
[0032] Then drying is performed to obtain activated nano titanium dioxide;
[0033] The nano titanium dioxide particle size is 30-50nm. This embodiment uses nano titanium dioxide to improve the anti-ultraviolet ability of polyphenylene sulfide monofilaments, and the structure can reduce the size of the sodium polyacrylate dispersed phase, improve the dispersibility of sodium polyacrylate in polyphenylene sulfide, and then help to form a moisture absorption path in the polyphenylene sulfide monofilament, thereby improving the hygroscopicity of the prepared monofilament. Preferably, nano-scale titanium dioxide particles with a smaller particle size are used, and the dispersion is more uniform.
[0034] Then, a silane coupling agent was prepared. The concentration of the silane coupling agent solution was 2%, and a mixed solution of ethanol and water was used, wherein the volume ratio of ethanol to water was 1:1.
[0035] Optionally, the silane coupling agent is γ-(methacryloyloxy)propyltrimethoxysilane. Add activated titanium dioxide into the silane coupling agent solution and react at 50° C. for a period of time to prepare modified titanium dioxide.
[0036] Then, sodium acrylate grafted titanium dioxide is prepared, wherein acrylic acid can be prepared into an acrylic acid solution with a concentration of 18%, placed in a beaker cooled with ice water, and stirred in a ventilated place, and then sodium hydroxide solution is slowly added dropwise to the acrylic acid solution to obtain a sodium acrylate solution with a neutralization degree of 80%; then a certain amount of initiator is added and placed at a temperature of about 60°C for reaction and stirring, and the preferred initiator is K2S2O8, until the system becomes viscous, and the product is taken out and precipitated with ethanol, washed, and dried, and the drying temperature is preferably about 60°C to obtain sodium polyacrylate grafted nano titanium dioxide.
[0037] In this embodiment, sodium polyacrylate is grafted with titanium dioxide in the form of grafting. The sodium polyacrylate itself contains a large number of polar hydrophilic groups, which have affinity for water. At the same time, sodium polyacrylate is used to inhibit the crystallization of polyphenylene sulfide, making it easier to stretch the monofilament, and the strength of the monofilament is also increased. At the same time, the hydrophilicity and hygroscopicity of the composite monofilament are improved; the polymer grafting method can inhibit the agglomeration of nano-titanium dioxide and improve its dispersibility, thereby enhancing the mechanical properties of the polyphenylene sulfide monofilament.
[0038] In the above steps, the sodium polyacrylate grafted titanium dioxide material is prepared, and the polyphenylene sulfide resin slice and the light stabilizer are mixed, wherein the light stabilizer is UV-3346 or UV-1084, and the mass ratio of the polyphenylene sulfide resin slice, the sodium polyacrylate grafted nano-titanium dioxide and the light stabilizer is (95-98): (4-1): (4-1); the density of the polyphenylene sulfide resin slice is 1.34-1.36 g / cm 3 The polyphenylene sulfide resin slices and the sodium polyacrylate grafted nano-titanium dioxide need to be fully dried before mixing, for example, the polyphenylene sulfide resin slices are dried at 130° C. for at least 15 hours, and the sodium polyacrylate grafted nano-titanium dioxide is dried at 100° C. for at least 10 hours.
[0039] The above materials are mixed and added into a single screw extruder for melt extrusion spinning at a spinning speed of 750 m / min, and then cooled, stretched and high-temperature heat-set before winding to form polyphenylene sulfide monofilaments, wherein the single screw spinning machine comprises a feed port, a screw zone and a spinning manifold arranged in sequence, the screw zone is provided with a melt extrusion port, and the melt extrusion port is connected to the spinning manifold through a bend pipe,
[0040] The melt extrusion port is provided with a melt metering pump, and the pump supply amount of the melt metering pump is 20-23 g / min.
[0041] The screw area of the single-screw spinning machine is divided into five zones, and the temperatures of the five zones are not exactly the same. The temperatures of the zones are: 300°C for zone 1, 310°C for zone 2, 310°C for zone 3, 315°C for zone 4, and 320°C for zone 5. The melt pressure of the melt metering pump is 8MPA, and the initial pressure of the spinneret is less than or equal to 12MPA. The melt extrusion port is connected to the spinning manifold through an elbow, and the temperature inside the elbow and the spinning manifold is set at 300°C.
[0042] The subsequent drawing step is set with two-stage drawing, and the drawing temperatures of the first and second stages are set to 115°C and 125°C respectively, with a total drawing multiple of 5.6 times. After a high-temperature heat setting process at a temperature of 180°C, the highly hygroscopic polyphenylene sulfide monofilament is wound. The temperature in the above embodiment is the set temperature, and the actual temperature can fluctuate by 3°C.
[0043] This embodiment also provides a highly hygroscopic polyphenylene sulfide monofilament prepared by the above preparation method.
[0044] According to the above method, five embodiments are given below:
[0045] Example 1
[0046] Step 1: Select nano-TiO2 with a particle size of 30 nm, weigh 10 g of nano-TiO2, soak it in 100 ml of sodium methane sulfonate solution with a mass fraction of 5% for 4 h, activate it, and obtain activated nano-TiO2 after drying; prepare ethanol and water into a mixed solution with a volume ratio of 1:1, measure 500 ml of the mixed solution, add silane coupling agent (γ-(methacryloyloxy)propyltrimethoxysilane, referred to as MPS) to make a 2% MPS solution, and weigh 5 g of activated nano-TiO2 and add it to the MPS solution, react at 50°C for 24 h to obtain modified MPS-TiO2;
[0047] Step 2: Prepare acrylic acid into an acrylic acid solution with a concentration of 18%, place it in a beaker cooled with ice water, and stir it under a fume hood. Then slowly add sodium hydroxide solution to the acrylic acid solution to obtain a sodium acrylate solution with a neutralization degree of 80%, and store it in a brown bottle; take 3.2g of modified MPS-TiO2 and put it in a beaker, add 50ml of the above sodium acrylate solution, and then add 0.3g of K2S2O8 as an initiator; place it at a temperature of 60℃ to react for 1.5h, and stop stirring when the system becomes viscous; take out the product, precipitate it with ethanol, wash it, and dry it at 60℃ to obtain sodium polyacrylate grafted nano-TiO2.
[0048] Step 3: Select a density of 1.36 g / cm 3 Polyphenylene sulfide resin chips, dried polyphenylene sulfide resin chips and sodium polyacrylate grafted nano-TiO2, polyphenylene sulfide resin chips and sodium polyacrylate grafted nano-TiO2 need to be dried before spinning, polyphenylene sulfide resin chips need to be dried at 130℃ for 15 h, and sodium polyacrylate grafted nano-TiO2 needs to be dried at 100℃ for 10 h. 95 parts of polyphenylene sulfide resin chips, 4 parts of sodium polyacrylate grafted nano-TiO2 and 1 part of light stabilizer UV-3346 are mixed evenly and added to the feeding port of the single-screw spinning machine for melt extrusion. The screw of the single-screw spinning machine is divided into five zones, and the temperatures of each zone of the screw are: 300℃ in zone 1, 310℃ in zone 2, 310℃ in zone 3, 315℃ in zone 4, and 320℃ in zone 5; the melt metering pump is used for metering, the pump supply is 23 g / min, the melt pressure is 8 MPa, and the initial pressure is controlled at 12 MPa during spinning. The melt is sent to the spinning box through the elbow for spinning. The temperature of the elbow and the box is set at 300℃, the spinning speed is 750 m / min, and the drawing is carried out through cooling, drawing, and two-stage drawing. The first and second-stage drawing temperatures are set at 115℃ and 125℃ respectively, and the total drawing multiple is 5.6 times. After a high-temperature heat setting process at 180℃, the highly hygroscopic polyphenylene sulfide monofilament is wound.
[0049] Example 2
[0050] Nano-TiO2 with a particle size of 40 nm was selected, and the mass ratio of polyphenylene sulfide resin slices, sodium polyacrylate grafted nano-TiO2 and light stabilizer UV-3346 was 96:3:1. The remaining steps were the same as those in Example 1.
[0051] Example 3
[0052] Nano-TiO2 with a particle size of 40 nm was selected, UV-1084 was selected as a light stabilizer, the mass ratio of polyphenylene sulfide resin slices, sodium polyacrylate grafted nano-TiO2 and light stabilizer was 98:1:1, and the remaining steps were the same as in Example 1.
[0053] Example 4
[0054] UV-1084 was selected as the light stabilizer, the mass ratio of polyphenylene sulfide resin slices, sodium polyacrylate grafted nano-TiO2 and light stabilizer was 95:1:4, and the remaining steps were the same as those in Example 1.
[0055] Comparative Example 1
[0056] Preparation of polyphenylene sulfide monofilament:
[0057] Acrylic acid is prepared into an acrylic acid solution with a concentration of 18%, placed in a beaker cooled with ice water, and stirred under a fume hood. Then, sodium hydroxide solution is slowly added dropwise to the acrylic acid solution to obtain a sodium acrylate solution with a neutralization degree of 80%. Then, 0.3 g of K2S2O8 is added as an initiator, and the reaction is carried out at a temperature of 60°C for 1.5 hours. When the system becomes viscous, stirring is stopped. The product is taken out, precipitated with ethanol, washed, and dried at 60°C to obtain sodium polyacrylate.
[0058] The mass ratio of the polyphenylene sulfide resin slice, sodium polyacrylate and light stabilizer is 95:4:1, and the remaining steps are the same as those in Example 1.
[0059] Comparative Example 2
[0060] Preparation of polyphenylene sulfide monofilament:
[0061] Acrylic acid was prepared into an acrylic acid solution with a concentration of 18%, placed in a beaker cooled with ice water, and stirred under a fume hood. Then sodium hydroxide solution was slowly added dropwise to the acrylic acid solution to obtain a sodium acrylate solution with a neutralization degree of 80%; then 0.3 g of K2S2O8 was added as an initiator, and the solution was reacted at 60°C for 1.5 hours. When the system became viscous, stirring was stopped; the product was taken out, precipitated with ethanol, washed, and dried at 60°C to obtain sodium polyacrylate.
[0062] The mass ratio of polyphenylene sulfide resin slices, sodium polyacrylate, nano-TiO2 and light stabilizer is 95:2.95:1.05:1, and the remaining steps are the same as those in Example 1.
[0063] The relevant parameters of the monofilament in each embodiment and comparative example are given below:
[0064]
[0065] By comparing Example 1 with Comparative Example 1, it can be concluded that the strength of the composite monofilament in Example 1 is much higher than that of the composite monofilament in Comparative Example 1, and the moisture regain is similar. Since the composite monofilament in Example 1 is blended with sodium polyacrylate by nano-TiO2 grafting, during the spinning process, nano-TiO2 helps to reduce the size of the dispersed phase of sodium polyacrylate, improve the dispersibility of sodium polyacrylate in polyphenylene sulfide, and help to form a moisture absorption path in the polyphenylene sulfide monofilament, thereby enhancing the mechanical properties and improving the hygroscopicity. However, the sodium polyacrylate content added in Comparative Example 1 is relatively high, the compatibility is relatively poor, and the composite monofilament strength is relatively low;
[0066] Comparing Example 1 with Comparative Example 2, the composite monofilament breaking strength in Comparative Example 2 is 3.75 cN / dtex, which is lower than that in Example 1. Since Comparative Example 2 does not use polymer grafting for melt spinning, nano-TiO2 agglomerates in the melt, resulting in a decrease in the mechanical properties of the monofilament. The standard moisture regain of polyphenylene sulfide monofilament is close to 0.1%, and the hygroscopicity is poor. With the increase of the mass fraction of sodium polyacrylate grafted nano-TiO2, the moisture regain of the composite monofilament gradually increases. When the mass fraction of sodium polyacrylate grafted nano-TiO2 is 4%, the moisture regain of the polyphenylene sulfide composite monofilament is 5.56%.
[0067] It should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like used above to indicate orientations or positional relationships are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention; the orientation words "inside" and "outside" refer to the inside and outside relative to the contours of the components themselves. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0068] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the present application.
Claims
1. A method for preparing highly hygroscopic polyphenylene sulfide monofilament, characterized in that: The method comprises: Preparation of modified titanium dioxide: activating a certain mass of nano titanium dioxide to obtain activated nano titanium dioxide, providing a silane coupling agent solution, adding the activated nano titanium dioxide to the silane coupling agent solution, reacting at a set temperature for a set time to obtain modified titanium dioxide, wherein the silane coupling agent is γ-(methacryloyloxy)propyltrimethoxysilane The "activating a certain mass of nano-titanium dioxide to obtain activated nano-titanium dioxide" includes: immersing a certain mass of nano-titanium dioxide in a sodium methane sulfonate solution with a mass fraction of 5% for a certain period of time for activation treatment; Then drying is performed to obtain activated nano titanium dioxide; Preparation of sodium acrylate grafted nano titanium dioxide: providing a sodium acrylate solution, placing the modified titanium dioxide into the sodium acrylate solution, adding an initiator to carry out stirring reaction until it becomes viscous, precipitating, washing and drying the product to obtain sodium polyacrylate grafted nano titanium dioxide; Preparation of highly hygroscopic polyphenylene sulfide monofilaments: uniformly mix a certain mass fraction of polyphenylene sulfide resin slices, the sodium polyacrylate grafted nano-titanium dioxide, and a light stabilizer, add the mixture into a single-screw spinning machine, and perform melt extrusion spinning to obtain highly hygroscopic polyphenylene sulfide monofilaments.
2. The method for preparing highly hygroscopic polyphenylene sulfide monofilament according to claim 1, characterized in that: in, The particle size of the nano titanium dioxide is 30-50 nm.
3. The method for preparing highly hygroscopic polyphenylene sulfide monofilament according to claim 1, characterized in that: The concentration of the silane coupling agent solution is 2%, and a mixed solution of ethanol and water is used, wherein the volume ratio of ethanol to water is 1:
1.
4. The method for preparing highly hygroscopic polyphenylene sulfide monofilament according to claim 1, characterized in that: The light stabilizer is UV-3346 or UV-1084.
5. The method for preparing highly hygroscopic polyphenylene sulfide monofilament according to claim 1, characterized in that: The mass ratio of the polyphenylene sulfide resin slice, the sodium polyacrylate grafted nano-titanium dioxide and the light stabilizer is (95-98): (4-1): (4-1); Wherein, the density of the polyphenylene sulfide resin slice is 1.34-1.36 g / cm 3 .
6. The method for preparing highly hygroscopic polyphenylene sulfide monofilament according to claim 1, characterized in that: The single-screw spinning machine comprises a feed port, a screw zone and a spinning manifold which are arranged in sequence, wherein the screw zone is provided with a melt extrusion port, and the melt extrusion port is connected to the spinning manifold through a bend pipe. The melt extrusion port is provided with a melt metering pump, and the pump supply amount of the melt metering pump is 20-23 g / min.
7. A highly hygroscopic polyphenylene sulfide monofilament prepared by the method for preparing highly hygroscopic polyphenylene sulfide monofilament according to any one of claims 1 to 6.
Citation Information
Patent Citations
Cupric oxide nanoparticle having superior water dispersibility and preparation thereof
CN101327945A
Method of coating titanium dioxide with polymers
CN106589204A